Dictionary of education - Lawton, Denis (Hodder and Stoughton, 1996)
This book is intended to explore the particular meanings of some key words in education and training, and to analyse the relationships between those words. This book is divised into four sections: Section 1 provides brief discussions of some key ideas in education in the form of short essays which explore the meaning of concepts and relationships between concepts. Section 2 gives short definitions (and where necessary cross-references to other terms in Section 2 or to essays in Section 1). Section 3 contains some background historical information. Finally, Section 4 contains an up-to-date list of acronyms and abbreviations